Prevalence and factors associated with depression and anxiety in patients with psoriasis - Pollo, Camila Fernandes [UNESP]; Miot, Hélio Amante [UNESP]; Matos, Ticiane Dionízio de Sousa [UNESP]; de Souza, Jennifer Mellissa [UNESP]; Jorge, Marília Formentini Scotton [UNESP]; Miot, Luciane Donida Bartoli [UNESP]; Meneguin, Silmara [UNESP] (Wiley, 2021)
Objective: To identify the prevalence and factors associated with depression and anxiety in patients with psoriasis. Background: Psoriasis is a chronic, non-contagious, autoimmune inflammatory skin disease associated with psychological comorbidities. Design: A cross-sectional study conducted between March 2017–December 2018 in a dermatology infirmary and outpatient clinic of a public hospital in the inner State of São Paulo (Brazil). Methods: We used questionnaires with sociodemographic data and clinical history, the HADS (Hospital Anxiety and Depression Scale), DLQI-BRA (Dermatology Life Quality Index) and PASI (Psoriasis Area Severity Index). The correlations between variables were explored using multivariate techniques. STROBE checklist was applied as the reporting guideline for this study (File S1). Results: A total of 281 participants were included, of which the majority were female 146 (52%), with a mean age of 52.1 years (SD: 13.8), elementary school 154 (55%), married/cohabiting 209 (74%) and with low income 201 (72%). The median (p25–p75) time with the disease was 14 years (7–23). Regarding the quality of life, 31% of respondents reported being little affected by the disease. The prevalence of depression was 19% and that of anxiety was 36%. The multivariate analysis showed that the variables that influenced the anxiety and depression scores were as follows: DLQI-BRA, income, female sex, illness length and age. For the multiple correspondence analysis, the highest levels of anxiety and depression referred to women, middle age, lower income and low PASI. Conclusion: The prevalence of anxiety and depression symptoms was low. Female sex, income, age, illness length and quality of life were associated with anxiety and depression scores in patients with psoriasis. Relevance to clinical practice: Due to the scarcity of studies in the field of nursing with psoriasis patients, we believe these findings contribute to the reorganisation of the care provided, allowing nurses to timely identify mood disorders such as anxiety and depression and adopt the necessary measures to a service and/or specialised referral.
Keywords: anxiety; depression; dermatology; nursing; psoriasis